Nursing inter‐shift handover process in mental health settings: a best practice implementation project. Issue 1 (1st March 2013) - Poh, Chee Lien; Parasuram, Rajni; Kannusamy, Premarani
Abstract: Aims: Nursing inter‐shift handover remains an important traditional ritual in nursing. Timely and effective handover of critical information ensure continuity of patient care and safe delivery. This project took place in a tertiary mental health institution in Singapore. The project aims to (i) examine existing handover practices/process in the tertiary mental health institution; (ii) determine the strengths and limitations of the existing handover practice/process; and (iii) identify, implement and evaluate an evidence‐based nursing inter‐shift handover process to enhance patient safety and service delivery. Methods: This project was conducted in three phases using the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research Into Practice programmes. It was implemented over a period of 4 months from end of August 2011 to beginning of December 2011. Evidence‐based strategies such as town hall meetings and education sessions that reinforce proper handover techniques and its importance were implemented to enhance the handover processes and practices in four acute admitting wards. Pre‐ and post‐audit data were observed and recorded for each case handover during each inter‐shift handover session in four acute admitting wards. Results: The handover processes for 212 cases for four acute admitting wards were observed using the seven audit criteria. Post‐implementation audit findings show that compliance rate had improved significantly for the four criteria: an improvement of 49% compliance rate in the use of standardised documentation during shift handover session; an increase of 74% compliance rate in proper identification of patient at the start of each case report; a 31% increase in proper handing over of significant patient's history; and 18% increased compliance in providing detailed observation of patients. Conclusion: This project had shown that handover sessions can be made effective by translating evidence into practice through ongoing evidence‐based audit. Continuous evidence‐based evaluation, identification and implementation of nursing inter‐shift handover process are imperative to enhance patient safety and service delivery.